The Meaning and Measurement of the National Income and of Other Social Accounting Aggregates. - Murphy, Mary E.; Griffin, Charles H. (The Accounting Review, 1967)
Reviews the book "The Meaning and Measurement of the National Income and of Other Social Accounting Aggregates," by Edgar Z. Palmer.